Brønsted acid catalyzed enantioselective pericyclic reactions. Issue 29 (20th July 2017) - Sleet, Christopher E.; Tambar, Uttam K.; Maity, Pradip
Abstract: Pericyclic reactions can be challenging processes to render asymmetric, due to the concerted and non-polar nature of the transition states. Several examples have been reported in which a suitable catalyst binds to a heteroatom-containing substituent in the substrate and accelerates the reaction rate. The requirement of coordinating functionalized substrates has limited the generality of such asymmetric transformations. Multifunctional Brønsted acids are promising catalysts that represent a new paradigm in asymmetric pericyclic reactions. These chiral catalysts rely on multiple non-covalent interactions in the transition state for asymmetric induction, which has been utilized to activate more general substrate classes. In this review, we will cover recent advances in Brønsted acid catalyzed pericyclic reactions and discuss the impact of catalyst design on the expansion of substrate scope for highly enantioselective processes. Graphical abstract: